As empresas transnacionais no contexto dos direitos dos desastres - Silva, Daniela Carolina da Costa e (2024)
This thesis focuses on the importance of studying the Law of Disasters, which reveals itself as a new branch of law capable of establishing communication with different areas of science, through interdisciplinarity, being capable of predicting natural disasters or those caused by human action. Using risk analysis, it is possible to determine the vulnerability and resilience of communities, which increases the capacity to respond and implement protection. The research focused on the performance of transnational companies that operate in the operation of dams, especially ore dams, to verify preventive action and the application of disaster law in this context, in order to establish the importance and need to implement disaster policies. prevention, investigating everything from safety problems and responsibility of those who control the dam to the degree of commitment and patrimonial participation of the State and transnational companies. The analysis of the application of disaster law went beyond the issue of predictability and demonstrated that integration with the National Civil Defense Policy is necessary so that eduction, mitigation, response and recovery practices can be met and thus avoid or reduce damage. caused to the environment and life. The object of study was also to analyze the responsibility of transnational companies in the context of the National Dam Safety Policy. The methodology of qualitative bibliographic research was adopted, covering the works published to date and compared to current legislation. Focusing research on the regulation of transnational companies It is concluded that the concepts inherent to disaster rights are necessary and important, in their preventive approach to mitigating and preventing risks. In Brazil, the culture of prevention is in its infancy, which makes research important so that a new perspective can be taken regarding the actions of companies that in some way can have an impact on communities and the environment, especially transnational companies.